Nature's remarkable partners : wild poems for two voices - Bulion, Leslie, 1958- (Margaret Quinlin Books, 2026)
"These wild poems for two voices offer young readers an up-to-date peek at an intriguing array of symbiotic partnerships in nature. Most upper-elementary students are familiar with mutually beneficial partnerships in nature--butterflies and milkweed, for example, or clownfish and anemones. But award-winning science poetry author Leslie Bulion has delved into recent research on mutualism and found fresh examples of these relationships for young readers to investigate, including the egg-laying carrion beetle and its hitchhiking mite passengers, as well as the little goby fish that guards the pistol shrimp from predators in exchange for a safe haven. Reading aloud these clever verses for two voices will help young learners engage with and enjoy these marvels of nature, and notes in the back of the book shed more light on the diversity of poetic forms. In addition, brief science notes accompanying each featured partnership, and comprehensive back matter provides more opportunities for study. Robert Meganck's witty drawings add another layer of fun to this humorous gallery of perfect partners. This collection is ideal for cross-curricular learning, including units on biology, mutualism, and poetry" --